Is peripheral access for apheresis procedures underutilized in clinical practice?—A single centre experience. Issue 6 (15th September 2016) - Putensen, Daniel; Leverett, David; Patel, Bhavika; Rivera, Jasmin
Abstract: Background: The majority of reports regarding general vascular access choices for apheresis procedures argue that peripheral venous access should be considered first. However, the clinical reality appears to be different. While some procedures mandate central vascular access (e.g., therapeutic apheresis procedures in critically ill patients) and in some cases it is the patient's preference, we propose that the majority of elective procedures can be successfully performed peripherally. Purpose: To establish the feasibility and suitability of peripheral access for different apheresis procedures, undertaken in elective or emergency settings. Methods: The choice of vascular access devices and cannulation sites were analysed retrospectively from all apheresis procedures performed between January 2014 and December 2015 at a single institution. Results: Over 2 years a total of 3714 procedures were performed on 1061 patients. Absolute number of procedures (percentage) done peripherally: autologous and allogeneic hematopoietic progenitor cell harvest—400 (88%) and 458 (97%) respectively; mononuclear cell harvest—88 (93%); automated red cell exchange—1954 (80%); therapeutic plasma exchange—766 (26%); white blood cell depletion—48 (71%). Choice of vascular access for all procedures (absolute number [percentage]): peripheral and ultrasound‐guided peripheral deep vein cannulation—2683 (72%); central venous catheter access: femoral—331 (9%); jugular—511 (14%); subclavian—2 (<1%); double‐lumen port—187 (5%). Peripheral access in all apheresis procedures (emergency and elective) was 72%; for purely elective procedures this number increased to 80% to 97%, depending on the procedure. Conclusion: In our institution the majority of elective apheresis procedures are successfully performed using peripheral access.